PEMBUATAN BOAT IKAN 2 GT (GROSS TONNAGE) BAGI NELAYAN ACEH UNTUK PENINGKATAN TANGKAPAN IKAN MENUJU KETAHANAN PANGAN SELAMA PANDEMI COVID 19 - Nazaruddin Nazaruddin; Hendra Gunawan; Sabri Sabri; Iskandar Hasanuddin; Akram Tamlicha; Sarwo Edhy Sofyan; Ichsan Setiawan; Sofyan Sofyan (Jurnal Marine Kreatif, 2021)
Currently, the condition of fishing facilities for Acehnese fishermen is experiencing difficulties with raw materials due to the difficulty of obtaining good quality wood that is resistant to immersion in water. The Aceh boat measuring 7 meters long which is often referred to in the Acehnese language, namely Boat thep thep is one of the facilities used by Acehnese fishermen to carry out all activities. The application of composite materials or the method of making composites through Hand lay up and Spray up technology is very appropriate to solve this problem. The application of thermosetting polyester resin reinforced with E glass fiber has been proven to be able to increase the efficiency of using this method to become a superior product. This is very appropriate to answer the problems of Acehnese fishermen who have continued to experience losses in the operational cost sector. The main objective of the activity is to create an entrepreneurial partner unit that has the passion and expertise to increase competitiveness against fellow competitors who are directly related to the food security program. national. This is a manifestation of the use of campus academic research results for the community. The target of implementing this product-based science and technology program for the community is that in the short term, it will prioritize increasing the ability of partners and students to improve skills, improve skills in how to produce 2 GT Boats, with improving business management, and help create access to form new business worlds.